2009
DOI: 10.2478/v10003-009-0015-3
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Stimulated Luminescence and Thermoluminescence Dating of Archaeological Samples From Turkey

Abstract: Abstract:In this study, the potential of Infrared Stimulated Luminescence (IRSL) and thermoluminescence (TL) for dating the archaeological samples (pottery sherds and soil sample adhered to surface of human bone) which were taken from a Necropolis was investigated. Archaeological sherds taken from Nusaybin (Mardin, Turkey), an archaeological site of archaic and Hellenistic period (from 330 BC to 30 AD), were dated. Samples were prepared by the fine grain technique and paleodose values were estimated by using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Uncertainties obtained are in good agreement with literature (Hütt et al, 2001;Benea et al 2007;Veronese et al 2008, Meriç et al 2009). The obtained results were summarized in Table 1.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Uncertainties obtained are in good agreement with literature (Hütt et al, 2001;Benea et al 2007;Veronese et al 2008, Meriç et al 2009). The obtained results were summarized in Table 1.…”
Section: Resultssupporting
confidence: 80%
“…To the best of our knowledge, no other luminescence dating study has been reported in this region thus far, although there exist some luminescence dating studies conducted on archeological samples from different archeological sites (Meriç et al 2009;Kıyak et al, 2010). Therefore, the present work was the first application of the thermoluminescence dating technique for the site.…”
Section: Resultsmentioning
confidence: 99%
“…Cathode-luminescence, CL, is produced when an electron beam is accelerated and implanted into the sample. Thermoluminescence, TL, arises when electrons trapped in a sample are released by heat and then recombine emitting light [26]. SRO obtained by LPCVD and annealed at 1,100 • C has shown PL, CL, EL, and TL [27].…”
Section: Luminescencementioning
confidence: 99%